Characteristics of Patients with Diminished Ovarian Reserve Undergoing in Vitro Fertilization (IVF) at Hasan Sadikin Hospital from 2019-2023 - Iqbal Anugrah Fitriyanto; Anita Rachmawati; Akhmad Yogi Pramatirta (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aimed to describe the characteristics of patients with diminished ovarian reserve undergoing in vitro fertilization (IVF) to improve understanding of its implications for infertility.Methods: Cross-sectional descriptive study using medical records of patients who underwent IVF at Dr. Hasan Sadikin General Hospital (RSHS) from 2019 to 2023. Analyzed variables included age, education level, occupation, duration of marriage, body mass index, Anti-Müllerian hormone (AMH) level, and ovarian stimulation protocol.Results: A total of 57.14% of the 55 patients were aged 35 – 40 years, 87.5% nulliparous, and 55.36% had a body mass index greater than 24.9 kg/m2. The percentage that held a bachelor’s degree was 64.29%, and 55.36% had AMH levels below 1.1 ng/ml. A total of 78.57% received a short stimulation protocol, and 21.43% received a long stimulation protocol.Conclusion: Most patients with diminished ovarian reserve undergoing IVF at RSHS (2019 – 2023) were aged 35 – 40, nulliparous, obese class I–II, AMH value <1.1 ng/ml, and were subjected to a short IVF protocol.Karakteristik Pasien dengan Diminished Ovarian Reserve yang Melakukan In Vitro Fertilization (IVF) di Rumah Sakit Hasan Sadikin pada Tahun 2019 – 2023AbstrakTujuan: Penelitian ini bertujuan menggambarkan karakteristik pasien dengan cadangan ovarium menurun yang menjalani fertilisasi in vitro untuk meningkatkan pemahaman tentang implikasi cadangan ovarium menurun pada infertilitas.Metode: Metode yang digunakan dalam penelitian ini adalah deskriptif observasional potong lintang yang menggunakan data rekam medis pasien yang menjalani fertilisasi in vitro di Rumah Sakit Hasan Sadikin (RSHS) periode 2019 – 2023. Variabel yang dianalisis meliputi usia, tingkat pendidikan, pekerjaan, lama menikah, indeks massa tubuh, kadar hormon anti-Müllerian, dan protokol stimulasi ovarium.Hasil: Hasil penelitian menunjukkan bahwa dari 55 pasien, 57,14% berusia 35 – 40 tahun, 87,5% belum pernah melahirkan, 55,36% memiliki indeks massa tubuh lebih dari 24,9 kg/m2, 64,29% berpendidikan sarjana, dan 55,36% memiliki kadar hormon anti-Müllerian kurang dari 1,1 ng/ml. Sebanyak 78,57% menjalani protokol stimulasi pendek dan 21,43% menjalani protokol stimulasi panjang.Kesimpulan: Sebagian besar pasien dengan cadangan ovarium menurun yang menjalani fertilitasi in vitro di RS Dr. Hasan Sadikin (201 – 2023) berusia 35 – 40 tahun, nullipara, obesitas kelas I–II, nilai AMH <1.1 ng/ml dan menjalani protokol IVF pendek.Kata kunci: Anti-mullerian hormone; diminished ovarian reserve; FSH; infertilitas; in vitro fertilization (IVF), teknologi reproduksi berbantu